Fiber Wireless (FiWi) Access Network Planning & Deployment using Reptile Search Algorithm - Chouhan, Nitin; Bhatt, Uma Rathore; Bhat, Vijay (International Journal of Sensors Wireless Communications and Control, 2023)
Aim: The aim of this study is the deployment of components in an efficient manner to make a cost-effective FiWi network. Background: Fiber Wireless access network is the boost to broadband access technology for providing network services to Internet users at a lower cost. Deployment of components in FiWi access network is very crucial since it affects the deployment cost and network performance. Objective: We investigate the planning process for efficient placement of components in FiWi access networks. For optimizing the position of components (wireless routers and ONUs) in the network, a novel nature inspired Reptile Search Algorithm (RSA) is proposed in the paper. Methods: Extensive simulation is carried out to implement proposed work. A simulation model and code is developed in MATLAB to get the optimized position of components for existing and proposed algorithms. Results: We compare the performance of proposed algorithm with existing algorithm. The obtained results show that the proposed algorithm has superior performance than the existing algorithm. Conclusion: The present work optimizes the position of components using RSA algorithm. RSA returns the lower number of required wireless routers/ONUs, lesser TCD, increased AONUC, fast convergence rate, lesser execution run time than WSSA algorithm. The outcome of the paper highlights the importance of the proposed work in network planning and component deployment in FiWi access network.
Keywords: Network planning